Interpreting the Impact of a Professional Development Program: Views of EntrepreneurFellows from Kenya, South Africa, and UgandaOne Year Later - Gabriella D. Bragoli; M. Craig Edwards; Shida R. Henneberry; Craig E. Watters (Journal of International Agricultural and Extension Education, 2021)
We conducted a qualitative study that examined the experiences of entrepreneurs who participated in a five-week-long professional development and cultural exchange fellowship program. The Entrepreneur Fellows represented three Sub-Saharan African nations and an array of enterprises, including agriculture and its allied fields, youth development organizations, and social ventures. The study assessed the post-fellowship experiences of the participants, especially regarding their enterprise-related goals, motivations and challenges, community-level impacts, as well as networking and communication practices. Analysis of data derived from 11 semi-structured interviews revealed three overarching themes and nine subthemes. The Entrepreneur Fellows were committed tolife-long learning and sharing information, gained new business skills, and expanded their global networks. The Fellows valued their program participation and viewed it as a mark of success. Further, participants were motivated not only by the growth of their enterprises, but also the potential to positively impact their communities. Our findings imply the need for multi-year, longitudinal research, including economic impact data from the Fellows’ enterprises. We also recommend that similar programming be supported and delivered in the future.
Keywords: enterprise development; entrepreneurship; fellowships; Sub-Saharan Africa